Strategi Produksi On Air dan Digital Promo Indosiar dalam Menarik Perhatian Pemirsa Mega Film Asia - Hidayah, Deviana Rahma; Dharmawan, Leonard (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the production strategy of on-air and digital promotions in attracting viewers' attention to the Mega Film Asia program at Indosiar. The method used is a descriptive qualitative approach with data collection techniques through in-depth interviews and participatory observation. The promotional strategy was analyzed using the AIDA model (Attention, Interest, Desire, Action) to identify the stages in building interest to encourage viewing actions from viewers. In addition, the Uses and Gratifications theory was used to understand the motivations and needs of viewers in consuming the promotional content presented. The results show that the promotion strategy is carried out in an integrated manner through synergy between the on-air promo division and the digital division, which results in consistent and adaptive promotional content according to the characteristics of each media. Promotion functions not only as a reminder of the airing schedule, but also as a trigger for viewers' initial interest through a strong emotional and visual approach. In conclusion, the success of the Mega Film Asia program promotion lies in cross-platform collaboration and the development of a production strategy that is responsive to the dynamics of audience behavior in the digital era.